Special drawing rights (SDRs) : the first international money - Wilkie, Christopher (Oxford : Oxford University Press, 2012)
'Special Drawing Rights' have recently re-emerged as a potential source of support and stability for the world economy, and this volume looks at the history of SDRs as well as the changing roles of the United States and the International Monetary Fund and the nature of the relationship between them.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Keywords: International Monetary Fund -- History; Special drawing rights -- History; United States -- Foreign economic relations